Pembuatan Papan Edukasi Sejarah Cagar Budaya Meriam Jepang di Kelurahan Baru Tengah, Balikpapan - Rahayu Sri Waskitoningtyas; Jordy Saputra; Deanisa Putri Adinda; Amelia Dwi Anita; Grasela Tulung Allo; Arman Sulfian Dani; Deo Ramadhan Pramudia; Arzelingga Muharam; Habil Ashari; Elok Fatoroni; Arpan Purba (Abdimas Universal, 2024)
Cultural heritage is the nation's cultural wealth as a form of thought and behavior in human life which is important for the understanding and development of history, science and culture in social, national and state life so it needs to be preserved and managed appropriately through efforts to protect, develop and utilize in order to advance national culture for the greatest prosperity of the people. After conducting a survey, it was found that there was one cultural heritage that did not have an educational board on the history of the Japanese cannon cultural heritage at that location, making visitors who came to the location of the Japanese Cannon Cultural Heritage less aware of when and how the history of the Japanese cannon came to be in Balikpapan City. Therefore, this educational board on the history of Japanese cannons was created to make it easier for visitors who come to the Japanese Cannon Cultural Heritage location to find out the history of these cannons. The educational board is made with galvanized iron and an acrylic board written on with a white marker with a black acrylic base color. This educational board is placed in front of the Japanese cannon location with a height of 1.5meters to make it easier for children to read.